Construction in Japan from the Perspective of Sharia Business Management Kurotaki Constructions Co. Ltd. 2024 - Akhmad Abdul Faqih Alfajari; Mohamad Maftuh Fauzi (International Forum of Researchers and Lecturers, 2025)
This study discusses the construction system in Japan from the perspective of Sharia business management. Japan is known for its high construction standards, advanced technology, and disciplined work system. The study aims to analyze how Sharia business principles can be applied in the construction industry in Japan, particularly in workforce management, finance, and business ethics. Using a qualitative descriptive method, this research explores the firsthand experiences of construction workers in Japan and the policies that support Sharia business practices in the industry. The findings indicate that there are opportunities to implement Sharia concepts in human resource management and financial transparency.